Climate Change Adaptation and Mitigation: The Informal Sector’s Experience in Ile-Ife, Nigeria - Joseph Igharo; Kelvin Olofu; Oluwatobi Tajudeen; Peter Oyelere; Albert Abegunde (Ruang, 2026)
Climate change increasingly threatens urban livelihoods, particularly within the informal sector, which often lacks institutional protection and adaptive capacity. Despite the importance of the informal economy in Nigerian cities, limited research has examined how informal sector operators perceive and respond to climate-related risks. This study explored how the informal sector activities are interacting with the climate change mitigation and adaptation strategies in Ile-Ife, Nigeria. A multi-stage sampling technique was employed to select 131 informal sector operators across three residential density zones (core, transition, and suburban areas). Data were collected through structured questionnaires and analyzed using descriptive statistical techniques including frequencies and percentages. The findings revealed that 61.8% of respondents experienced climate-related disruptions to their business activities, mainly due to irregular rainfall, flooding, and heat waves. These disruptions resulted in reduced daily sales, financial losses, and health challenges. Although about 79.4% of respondents reported awareness of climate change, the depth of understanding and implementation of adaptation strategies remained low. The most common adaptation strategy was modification of business shelters, while institutional support and climate-related training were limited. The study conclude that climate change significantly affects informal sector activities in Ile-Ife, while institutional responses remain inadequate. The study therefore recommended that there is a need for the integration of informal sectors concerns in the local climate policy models, expansion of awareness and training programmes by the government and increased access to credit facilities to strengthen resilience and enhance sustainable living.